First evidence that γ-tocotrienol inhibits the growth of human gastric cancer and chemosensitizes it to capecitabine in a xenograft mouse model through the modulation of NF-κB pathway - Manu, K.; Shanmugam, M.; Ramachandran, L.; Li, F.; Fong, C.; Kumar, Alan Prem; Tan, P.; Sethi, G. (American Association Cancer Research, 2012)
Purpose: Because of poor prognosis and development of resistance against chemotherapeutic drugs, the existing treatment modalities for gastric cancer are ineffective. Hence, novel agents that are safe and effective are urgently needed. Whether γ-tocotrienol can sensitize gastric cancer to capecitabine in vitro and in a xenograft mouse model was investigated. Experimental Design: The effect of γ-tocotrienol on proliferation of gastric cancer cell lines was examined by mitochondrial dye uptake assay, apoptosis by esterase staining, NF-κB activation by DNA-binding assay, and gene expression by Western blotting. The effect of γ-tocotrienol on the growth and chemosensitization was also examined in subcutaneously implanted tumors in nude mice. Results: γ-Tocotrienol inhibited the proliferation of various gastric cancer cell lines, potentiated the apoptotic effects of capecitabine, inhibited the constitutive activation of NF-κB, and suppressed the NF-κB–regulated expression of COX-2, cyclin D1, Bcl-2, CXCR4, VEGF, and matrix metalloproteinase-9 (MMP-9). In a xenograft model of human gastric cancer in nude mice, we found that administration of γ-tocotrienol alone (1 mg/kg body weight, intraperitoneally 3 times/wk) significantly suppressed the growth of the tumor and this effect was further enhanced by capecitabine. Both the markers of proliferation index Ki-67 and for microvessel density CD31 were downregulated in tumor tissue by the combination of capecitabine and γ-tocotrienol. As compared with vehicle control, γ-tocotrienol also suppressed the NF-κB activation and the expression of cyclin D1, COX-2, intercellular adhesion molecule-1 (ICAM-1), MMP-9, survivin, Bcl-xL, and XIAP. Conclusions: Overall our results show that γ-tocotrienol can potentiate the effects of capecitabine through suppression of NF-κB–regulated markers of proliferation, invasion, angiogenesis, and metastasis.